Perancangan Mesin Press Tahu Sistem Pnuematik Dengan Kapasitas 50 Kg - Elvis Adril; Asmed Asmed; Fardinal Fardinal; Yulia Sasmita Angraini (Jurnal Teknik Mesin, 2021)
This pneumatic system tofu press machine is a press machine that is used to compress tofu starch with a capacity of 50 kg to make tofu that is ready to be marketed. The pneumatic system tofu press machine is made to make it easier to press tofu. Previously, tofu was pressed manually, namely by using a stone as a tofu press which resulted in the length of the tofu compaction process. Pressing with stones can also cause work accidents. This tofu press machine uses pneumatics as a punch driver which will press the tofu. The way this tofu machine works is by pressing the on button on the machine then the punch will move down towards the tofu essence and press the tofu. Punch paused for a moment to make sure the tofu blended in perfectly. Then press the off button on the machine to return the punch to its original position. This pneumatic system tofu press machine can reduce work accidents, lighten work, shorten processing time and is also more hygienic because it uses air as a punch driver.